Wearable bio-inspired pulsating-flow cooling for live garments based on a novel design of ferrofluid micro-valve - Tang, Jiawei; Luk, Patrick Chi-Kwong (MDPI, 2022)
Temperature-related frustrations, such as heat exhaustion, heat stroke, hypothermia, and frost damage, are some of the most prevalent health risks encountered by humans. The aggravation may be lethal for individuals who reside or work in conditions of protracted and high temperature. Temperature-control technologies, such as underfloor heating and air conditioners, have been studied and applied to give individuals with a pleasant and, more crucially, an endurable temperature. However, it may be challenging to install these technologies in an exterior or enclosed space. In addition, they are inflexible for individual requirements, such as mobility and personal-temperature management. A wearable bio-inspired pulsing-flow (discontinuous) cooling system, which can significantly enhance cooling performance, is proposed in this work. The proposed system is implemented with valves to generate pulsating flows. Given that traditional mechanical-valve actuation systems continue to face limits in terms of switching frequency, interface wear loss, and size limitations for wearable-garment applications, a ferrofluid-based shape-controllable micro-valve is proposed to reduce the size and weight of the cooling system. An empirical approach is adopted to avoid the extensive computational simulation of the thermo fluidic dynamics involved, so that efforts can be focused on the design of an innovative scaled prototype built from ferrofluid valves positioned in a specific array of the cooling tubes. This allows the performance of continuous and pulsating cooling-flow systems to be compared on the same flow rate baseline. The results demonstrate that the proposed technology not only delivers superior cooling efficiency, but also has the potential to provide individualized temperature regulation in a “live” garment.
Keywords: bio-inspired flow; pulsation cooling; wearable temperature conditioning; live garment; empirical approach